Impact of risk factors for major cardiovascular diseases: a comparison of life-time observational and Mendelian randomisation findings - Johan Ärnlöv; Johan Sundström; Lars Lind; Martin Ingelsson (Open Heart)
Background This study compared the strength and causality of associations between major risk factors for cardiovascular disease (CVD) and the four major CVDs: myocardial infarction, ischaemic stroke, heart failure and atrial fibrillation. Both a long-term follow-up in an observational cohort and Mendelian randomisation (MR) were used for this aim.Methods In the Uppsala Longitudinal Study of Adult Men study, 2322 men, all aged 50 years, were assessed for CVD risk factors and then followed for four decades regarding incident CVDs. The two-sample MR part used public available Genome-Wide Association Study (GWAS) data.Results In multivariate analyses, systolic blood pressure was overall by far the most important risk factor, since it was related to all four CVDs, both in observational and MR analyses. Body mass index was the second most overall important risk factor, being linked to all four CVDs, except ischaemic stroke, both in observational and MR analyses. Smoking was an important risk factor for ischaemic stroke and heart failure, both in observational and MR analyses, while low-density lipoprotein-cholesterol mainly was related to myocardial infarction. Diabetes was mainly a causal risk factor for incident myocardial infarction and heart failure. Neither HDL-cholesterol nor triglycerides were of major importance as risk factors in these multivariable models.Conclusion By combining long-term observational data with genetic data, we show that the impact and causal role of specific established cardiovascular risk factors varies between different major CVDs. Systolic blood pressure was causally related to all four cardiovascular outcomes and was therefore, overall, the most important risk factor.